Features of investigation of atmospheric air pollution - Oliynychuk, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
Atmospheric air pollution as a crime against the environment is considered. Researchers’ views on the categories related to the investigation of this offense are analyzed. The importance of proper planning of actions of law enforcement officials for the successful detection of crimes against the environment committed by air pollution is substantiated. The peculiarities of individual investigative actions in the investigation of air pollution are identified and the relevant author’s conclusions are made.